Norms, Emotions, and Culture in Human Cooperation and Punishment: Theory and Evidence - Sanjit Dhami; Mengxing Wei (Center for Economic Studies and ifo Institute (CESifo), 2023)
We consider the psychological and social foundations of human contributions and punishments in a voluntary contributions mechanism with punishment (VCMP). We eliminate 'dynamic economic linkages' between the two stages of our 'modified' VCMP to rule out other potential explanations. We use a beliefs-based model, rooted in psychological game theory, to derive rigorous theoretical predictions that are then tested with pre-registered experiments in China and the UK. Social norms, culture, and endogenous emotions are the key determinants of contributions and punishments. The emotions of shame, frustration, and anger, play a key role in our theoretical and empirical analysis through 'dynamic psychological linkages'. We provide potential microfoundations for the inherent human tendency to follow social norms and punish norm violators, while respecting boundedly rational strategic decision making.
Keywords: C91; C92; D01; D91; 330; cooperation and punishment; emotions-shame; frustration; anger; social norms; culture; bounded rationality